Censorship Activities in Far East in Early 20th Century (on Material of Cinema) - Y. G. Blagoder (Научный диалог, 2019)
The article is devoted to one of the aspects of the study of the structure and activity of censorship institutions in the Russian Empire in the early 20th century. The relevance of the problem is due to the fact that it is of great importance both for historical science and to attract the attention of the general public to the problems of formation and transformation of spiritual culture. The study is based on the documents of The Russian State Historical Archive of the Far East (Vladivostok), covering the little-studied aspects of the activities of censorship institutions and other public authorities of the Russian Empire, which influenced the development of mass culture in the cities of the Far East. Special attention is paid to determining the role of the Main Department for Press Affairs, the military governor of the Primorsky region and the inspector for press affairs of Vladivostok in improving the quality of products entering the illusions. It is noted that in the remote territories of the Russian Empire since 1897, thanks to foreign, later Russian entrepreneurs, cinema made the first steps. It is reported that the demonstration of films in illusions initially did not have great popularity among the local population. It is proved that the growth of interest in cinema is associated with the activation of various types of business activities: the development of film distribution, the construction of illusions, the organization of entertainment programs and film shows, advertising in periodicals. The author notes the negative consequences that were caused by the dependence of the repertoire of cinemas on the commercial interest of their owners. The article presents documents fragments testifying to the attention of state authorities, in particular, the Ministry of Internal Affairs of the Russian Empire, to this problem.